The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41380-023-01945-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of perioperative application of ketamine on postoperative depression: A meta-analysis of randomized controlled studies

Abstract: Ketamine, a commonly used general anesthetic, can produce rapid and sustained antidepressant effect. However, the efficacy and safety of the perioperative application of ketamine on postoperative depression remains uncertain. We performed a meta-analysis to determine the effect of perioperative intravenous administration of ketamine on postoperative depression. Randomized controlled trials comparing ketamine with placebo in patients were included. Primary outcome was postoperative depression scores. Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Other studies have also evaluated the effect of ketamine on mood ratings in surgical patients 46 ; however, numerous methodological limitations prevent direct comparison to studies of intravenous ketamine for depression in the psychiatric literature. Frequently, these trials were not conducted in a population likely to meet criteria for moderate-to-severe MDD 47-51 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also evaluated the effect of ketamine on mood ratings in surgical patients 46 ; however, numerous methodological limitations prevent direct comparison to studies of intravenous ketamine for depression in the psychiatric literature. Frequently, these trials were not conducted in a population likely to meet criteria for moderate-to-severe MDD 47-51 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidural analgesia will be employed for postoperative pain control, and the commencement time of surgery will be recorded. A prior meta-analysis has indicated that ketamine may ameliorate postoperative depression 24. However, in the study by Qiu et al ,3 no significant differences were observed in depression scores between the two groups during the follow-up period.…”
Section: Discussionmentioning
confidence: 90%
“…In terms of adverse effects, recent studies found that esketamine did not significantly increase the risk for nausea, vomiting, and psychotomimetic adverse events ( 12 , 15 ). On the other hand, a recent meta-analysis showed that perioperative use of ketamine reduced postoperative depression scores, but increased the risk of adverse effects including nausea and vomiting, headache, dizziness, and hallucination ( 14 ). In our study, the most commonly reported adverse events were mild PONV and dizziness, and the rates were similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies suggested that those side effects of ketamine may be attributed to S-ketamine, but not R-ketamine ( 7 , 13 ). However, recent clinical evidence showed that perioperative use of ketamine increased the risk of psychotomimetic adverse events ( 14 ), while esketamine did not significantly increase the risk ( 12 , 15 ).…”
Section: Introductionmentioning
confidence: 99%